Perception of teaching performance in the virtual learning environment - Guillermo Morales-Romero; Nicéforo Trinidad-Loli; Beatriz Caycho-Salas; Yanet Paucar-Manrique; César León-Velarde; Sofia Gamarra-Mendoza; Nestor Alvarado-Bravo; Almintor Torrez-Quiroz; Carlos Aliaga-Valdez; Florcita Aldana-Trejo (International Journal of Evaluation and Research in Education (IJERE), 2021)
This article aims to analyze the perception of the students of the professional school of business administration about the teaching performance in the virtual learning environment during the COVID-19 pandemic. When developing the research, it was determined that there is a good teaching performance, according to the perception of the students. However, it was identified that the factors of domain of the topic and class session management, present a better perception in this context of virtual learning; while the didactic strategies factor is the one that presents a not so favorable perception. In addition, through a comparative analysis, it was determined that the didactic strategies and planning factors have suffered a negative variation with respect to the perception per teacher, when moving from face-to-face to virtual learning, since, of the total of 17 specialty teachers, seven of them one negative variation. These results are validated by the linear regression test, where an R2 value of 0.965 is calculated, with respect to the didactic strategies factor. It means that this factor influences 96.5% on the perception of students with the global factor and an R2 value of 0.921 for the planning factor, which indicates an influence of 92.1%.